Process-based surface flattening method for laser peen forming of complex geometry. (28th April 2023) - Jiang, Jiancheng; Hu, Yongxiang; He, Xueting
Abstract: Laser peen forming (LPF) is a novel flexible forming process with several advantages, such as noncontact and high controllability, but it lacks a method to obtain the initial blank geometry based on its specific deformation behavior, limiting the application of the process. This study proposes a process-based surface flattening method to determine an optimal initial blank of complex geometry to accommodate the precise forming requirement. The process-based surface flattening method is developed based on the deformation behaviors of the laser-peened (LPed) and non-LPed zones with equal-strain and equal-area criteria, respectively. The objective surface is first flattened with the equal-area criterion, then the in-plane strain in LPed zones is loaded into the equal-area flattened blank. Because the in-plane strain is unknown before flattening, an optimization model is conceived to solve the in-plane strain in LPed zones based on the proposed equal-strain flattening method. Experiments are designed to validate the surface flattening methods regarding the LP-formed saddle surface as the objective with a known initial blank. The flattening blanks are quantitatively compared with the initial blank. The process-based flattening method presents the blank geometry with a mean absolute error (MAE) of 0.027 mm, while the geometry-based flattening method presents the result with a MAE of 0.398 mm, illustrating the process-based method can provide a more effective initial blank shape. Graphical abstract: Unlabelled Image